Serum 25-Hydroxyvitamin D Concentrations and Season-Specific Correlates in Japanese Adults - Akiko, Nanri; Leng, Huat Foo; Kazutosh, Nakamura; Ai, Hori; Kalpana, Poudel-Tandukar; Yumi, Matsushita; Tetsuya, Mizoue (Japan Epidemiological Association, 2011)
Background: Several lines of evidence indicate an important role for vitamin D in the prevention of a range of diseases. Blood vitamin D levels show clear seasonal variation; however, data on the determinants of vitamin D status for each season are limited. We investigated the association between lifestyle and serum vitamin D concentration by season in Japanese workers. Methods: Subjects were 312 men and 217 women aged 21 to 67 years who worked in municipal offices in Northern Kyushu, Japan and participated in a periodic checkup in July or November. Multiple linear regression analysis was used to examine the association between serum 25-hydroxivitamin D concentrations and lifestyle factors for each season. Results: Mean serum 25-hydroxyvitamin D concentration was 27.4 ng/ml (68.4 nmol/L) and 21.4 ng/ml (53.4 nmol/L) for workers surveyed in July and November, respectively (P < 0.001); the prevalence of vitamin D deficiency (<20 ng/ml) was 9.3% and 46.7%, respectively (P < 0.001). In November, dietary vitamin D intake (in both sexes) and nonsmoking and physical activity (in men) were significantly associated with higher concentrations of serum 25-hydroxyvitamin D. In summer, fish/shellfish intake was associated with higher serum 25- hydroxyvitamin D concentrations in women. Conclusions: Vitamin D deficiency is common in Japanese workers during seasons with limited sunlight. The lifestyle correlates of favorable vitamin D status in November were physical activity, dietary vitamin D intake, and nonsmoking.